SISTEM PENDIDIKAN GURUKULA - Suwendra, I Wayan (Jurnal Widya Sastra Pendidikan Agama Hindu, 2025)
Many Hindu Education experts in Bali and even in Indonesia do not know about the Gurukula Education system, therefore this literature study research was carried out. The problems of the Gurukula Education system that want to be expressed are: understanding, philosophical foundation, learning model and curriculum used. The research methods used are: Systematic literature study to identify, select, and analyze relevant literature with pre-established criteria. Meanwhile, the data analysis is through: meta-analysis, narrative synthesis, content analysis, framework synthesis, and realistic synthesis. The results of the research and discussion are: (1) the gurukula education system is a dormitory/ pasraman/pesantren education model, between teachers and students living together in a situation such as in a family with complete teachers, there is a school building, there are learning facilities and infrastructure, the curriculum follows modern schools, there is an educational level, and has a clear educational purpose, has a clear vision and mission, only the curriculum is dominated by Hindu religious material. (2) the philosophical foundations of the Gurukula education system are: Vedanta and Upanishads, the main goal of education is to attain spiritual wisdom and self-liberation (moksha), The education is holistic and focuses not only on the academic aspect but also on the formation of character, morality, and understanding of life as a whole, Integration with daily life, Students in the Gurukula system learn through direct experience, including daily tasks that help them understand responsibility and discipline, Simplicity and proximity to nature. (3) In the Gurukula education system, there are several learning models, namely: Observation-based learning and imitation, Personal learning and mentorship, Contextual learning, Spiritual learning and meditation, Discussion-based learning and dialogue. (4) Curriculum in the Gurukula education system: (a) Multi-disciplinary learning, (b) Character education, in addition to science, students are also taught moral values such as honesty, discipline, and respect for teachers and others, (c) Observation and imitation methods, students learn by observing and imitating the behavior of teachers and more experienced individuals, (d) Physical and mental integration, curriculum includes yoga practice, meditation, and physical activity for balance of body and mind, (e) Life-based learning, students not only learn theory but also engage in daily tasks, such as helping in community life.